2021
DOI: 10.4078/jrd.2021.28.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Bath Ankylosing Spondylitis Disease Activity Index is Associated With the Quality of Sleep in Ankylosing Spondylitis Patients

Abstract: Objective. High disease activity of ankylosing spondylitis (AS) is associated with poor sleep quality. The purpose of this study was to identify which of the representative tools for evaluating the disease activity of AS best reflect the quality of sleep. Methods. A total of 107 AS patients were enrolled in the study and the sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Age, sex, concomitant medication, erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP) level, Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Our cohort revealed higher mean ASDAS-CRP than mean ASDAS-ESR at both baseline and followup, which is consistent with a previous smaller study (12), although other studies have demonstrated lower ASDAS-CRP than ASDAS-ESR (9)(10)(11). In previous studies, the absolute difference between mean ASDAS-CRP and mean ASDAS-ESR ranged from zero (6)(7)(8) to one unit or above(9,10), while we found corresponding differences close to zero.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our cohort revealed higher mean ASDAS-CRP than mean ASDAS-ESR at both baseline and followup, which is consistent with a previous smaller study (12), although other studies have demonstrated lower ASDAS-CRP than ASDAS-ESR (9)(10)(11). In previous studies, the absolute difference between mean ASDAS-CRP and mean ASDAS-ESR ranged from zero (6)(7)(8) to one unit or above(9,10), while we found corresponding differences close to zero.…”
Section: Discussionsupporting
confidence: 91%
“…However, ASDAS-ESR showed a trend to classify higher numbers of patients in lower disease activity states compared to ASDAS-CRP and lower numbers of patients in higher disease activity states(4). Thereafter, some studies have reported equal mean ASDAS scores(6-8), whereas others have observed differences (9)(10)(11)(12). Hence, there may be clinically relevant discrepancies between the two versions and consequently between their cut-off values for disease activity states, which could impact on treatment decisions in a treat-to-target regimen.…”
Section: Introductionmentioning
confidence: 99%
“…1). The information from 18 studies is outlined in Table 1 [6,10,14,16,19,20,22,27,28,[34][35][36][37][38][39][40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…High disease activity of ankylosing spondylitis is associated with poor sleep quality. A positive correlation was reported between the ankylosing spondylitis disease activity indices Bath Ankylosing Spondylitis Disease Activity Index, Ankylosing Spondylitis Disease Activity Score with ESR, Ankylosing Spondylitis Disease Activity Score with CRP and sleep quality [17]. Pittsburgh Sleep Quality Index was developed in 1989 by Buysse et al [15] and Turkish validity and reliability study was performed by Ağargün et al [18].…”
Section: Discussionmentioning
confidence: 99%